PENGARUH BAURAN PEMASARAN JASA TERHADAP LOYALITAS NASABAH TABUNGAN SIMPEDES BANK BRI KANTOR UNIT SIMPANG HARU PADANG - HADINNISA, ISRAFRA ILMA (Jurnal Marketing, 2018)
The purpose of this study was to analyze: 1) The effect of the product on customer loyalty, 2) The influence of price on customer loyalty, 3) Effect of location / place on customer loyalty, 4) Effect of promotions on customer loyalty, 5) Effect of employees on customer loyalty, 6 ) the effect of the process on customer loyalty, 7) Effect of physical evidence on customer loyalty. This type of research is the study of causality. The population in this study were all savings customers Simpedes BRI Bank Office Simpang Haru Padang Units years 2010-2015 as many as 1893 accounts. 100 sample. The data analysis technique is descriptive analysis, test requirements and path analysis by t-test. The results of this study indicate that (1) the product positive and significant impact on customer loyalty Simpedes Customer BRI Banks Office Simpang Haru Padang Units, (2) the positive and significant impact on customer loyalty savings Simpedes BRI Banks Office Simpang Haru Padang Units, (3) location / place positive and significant impact on customer loyalty Simpedes BRI Banks Office Simpang Haru Padang Units, (4) the promotion of positive and significant impact on customer loyalty Simpedes BRI Banks Office Simpang Haru Padang Units, (5) the employee positive and significant effect on the customer loyalty Simpedes BRI Bank Office Simpang Haru Padang Units, (6) the positive and significant impact on customer loyalty savings Simpedes BRI Bank Office Simpang Haru Padang Units, (7) physical evidence positive and significant impact on customer loyalty Simpedes BRI Office Simpang Haru Padang Units.